FENOMENA PERILAKU MODERNISASI DALAM CORAK SENI LUKIS REALIS KONTEMPORER - M. KHALIFATUL SYUHADA, Ir. Drs. Heldi, M.Si, Drs. Idran Wakidi, M.Pd (Universitas Negeri Padang, 2015)
The work of the end of aims to visualization on the phenomena modernization pattern behavior in the painting of art realists contemporary, idea the creation of work painting of art through the phenomenon of the incident what is seen, felt and observed environment social, culture in the community. The impact of and a change that occurs in community social environment run in significant, so that can be perceived now, good positively and the impact a negative. A pattern the art of painting realists contemporary tended to be visualization portrait social life the community and young generation that experienced phenomena modernization as the principal subject who was poured through canvas with medium paint acrylic and oils and paints in pattern realists contemporary. Methods and approach of ideas via inspiration phenomenon thriving now. Phase and the process work started with a preparation, elaboration ideas, synthesis, and realize the concept, expressed concern for the next generation, The positive and negative impact modernization. Transformation change modernization this visualization through 10 ( ten ) the title of a work the art of painting in realist contemporary pattern.Keywords : The Phenomenon of Modernization, Contemporary Realist Painting